1999
DOI: 10.1177/135910539900400104
|View full text |Cite
|
Sign up to set email alerts
|

Health, Stress and Coping among Women Caregivers

Abstract: Informal family-based care of dependent adults places a significant burden on caregivers. The impact of caregiving on subjective wellbeing, preventive behaviours, lifestyle and employment is well documented, and there is good evidence for increases in risk factors for serious illness, although evidence on actual incidence of major illness varies between studies. The individual-based focus of much research on this topic has tended to obscure the social and cultural forces underlying the fact that the majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 91 publications
3
42
0
Order By: Relevance
“…Given the fact that women have always played a central role in maintaining the wellbeing of families, it is not surprising that female respondents expressed strong support for eldercare services than their male counterparts (Burnette & Mui, 1995;Iecovich, 2008;Lee, 1999). A positive association was found between age and the outcome variable.…”
Section: Resultsmentioning
confidence: 70%
“…Given the fact that women have always played a central role in maintaining the wellbeing of families, it is not surprising that female respondents expressed strong support for eldercare services than their male counterparts (Burnette & Mui, 1995;Iecovich, 2008;Lee, 1999). A positive association was found between age and the outcome variable.…”
Section: Resultsmentioning
confidence: 70%
“…A cross-check step was included, where two researchers examined the comments, with one categorising the comments and the second recoding a subset. Emerging themes not already encompassed by the empirical literature search 14 were then identified. Conducting a review of caregiving issues in older 13 and then mid-aged women 15 also allowed lifecourse nuances to emerge, such as differences in employment concerns, and caring for children and parents.…”
Section: Pattern Theme and Content Analysismentioning
confidence: 99%
“…13 The analysis examined data from Survey 1 of the 1921-26 cohort, after 10% of respondents were identified from quantitative survey data as being caregivers and recorded free-text comments about their caregiving experiences. Following an empirical literature review on the topic 14 , which provided a conceptual framework for the content analysis to follow, researchers analysed the free-text comments of 168 women. This work identified that caregivers had significantly lower levels of emotional wellbeing than noncaregivers, and felt stressed, rushed and pressured.…”
Section: Pattern Theme and Content Analysismentioning
confidence: 99%
“…It also indicates their awareness of insuf cient preparedness for providing parent care, need for help, and desire to relate more effectively with others. These ndings have implications for educational research to develop interventions that might facilitate lial maturity and the socialization of adult children into the role of caregiver in critical parent care situations.Epidemiological studies have revealed that approximately 5% to 10% of individuals over the age of 65 have problems with cognitive impairment (Lee, 1999). At least 70% of those with a dementing disorder receive care in the community, and nearly one third of these individuals receive their care from adult children, mostly daughters (Prescop, Dodge, Morycz, Schulz, & Ganguli, 1999).…”
mentioning
confidence: 99%